The effect of aluminium alloy secondary phases on aniline-based silane - Trueba, Mónica (2012)
Commercial wrought Al alloys with high content of intermetallic phases, namely, AA5083-H111, AA2024-T3 and AA7075-T6, were treated with N-(3-trimethoxysilylpropyl) aniline (AnSi) by a simple procedure. Characterization studies and corrosion experiments indicate that the hybrid film protection capacity is related in a complex way to the macromolecular network structure linked to the Al substrate composition. Nevertheless, barrier protection enhanced by a buffer effect and galvanic coupling, as aided by aniline units within the hybrid film, is indicated mostly. Results overall demonstrate synergistic effect against Al alloy corrosion by combining at a molecular level monomers of conducting polymers and silane functionalities.